Golgi apparatus dynamics during mouse oocyte in vitro maturation: effect of the membrane trafficking inhibitor brefeldin A - Moreno, Ricardo D. (2002)
We have studied Golgi apparatus dynamics during mouse oocyte in vitro maturation, employing both live imaging with the fluorescent lipid BODIPY-ceramide and immunocytochemistry using several specific markers (beta-COP, giantin, and TGN38). In germinal vesicle oocytes the Golgi consisted of a series of structures, possibly cisternal stacks, dispersed in the ooplasm, but slightly more concentrated in the interior than at the cortex. A similar pattern was detected in rhesus monkey germinal vesicle oocytes. These "mini-Golgis" were functionally active because they were reversibly disrupted by the membrane trafficking inhibitor brefeldin A. However, the drug had no visible effect if the oocytes had been previously microinjected with GTP-gamma-S. During in vitro maturation the large Golgi apparatus structures fragmented at germinal vesicle breakdown, and dispersed homogenously throughout the ooplasm, remaining in a fragmented state in metaphase-II oocytes. Similarly to what has been reported using protein synthesis inhibitors, the presence of brefeldin A blocked maturation at the germinal vesicle breakdown stage before the assembly of the metaphase-I spindle. These results suggest that progression of murine oocyte maturation may require functional membrane trafficking